2021
DOI: 10.3390/ijerph18094805
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Supplementation during Pregnancy Induces Sex and Region-Specific Alterations in the Offspring’s Brain Redox Status

Abstract: Research has shown the beneficial effects of naringin supplementation to adult rodents, which can ameliorate oxidative stress in disease models. However, evidence has demonstrated that polyphenol supplementation induced detrimental effects when consumed during sensitive periods of development, such as pregnancy. Therefore, we investigated the effect of maternal naringin supplementation during pregnancy on the offspring’s cerebral redox status. Pregnant Wistar rats were divided into control and naringin groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 94 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Naringin's ability to influence mitochondrial health highlights its potential to be used as a therapy in pregnancy‐related diseases and prevent offspring neuronal damage due to mitochondrial dysfunction and oxidative stress. In fact, recent findings have shown that both naringin and naringenin consumption during pregnancy may affect the offspring's brain redox status during postnatal life and induce energetic metabolism by modulating the electron transport system (ETS) and tricarboxylic acid (TCA) cycle enzymes in the pups' cerebellum early in life (August et al, 2020, 2021; August & dos Santos, 2020; Gindri dos Santos et al, 2021). However, the mechanisms by which naringin and naringenin affect offspring's mitochondria and whether such alterations might induce neurodevelopmental and behavioral defects that might prevent its use during pregnancy are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Naringin's ability to influence mitochondrial health highlights its potential to be used as a therapy in pregnancy‐related diseases and prevent offspring neuronal damage due to mitochondrial dysfunction and oxidative stress. In fact, recent findings have shown that both naringin and naringenin consumption during pregnancy may affect the offspring's brain redox status during postnatal life and induce energetic metabolism by modulating the electron transport system (ETS) and tricarboxylic acid (TCA) cycle enzymes in the pups' cerebellum early in life (August et al, 2020, 2021; August & dos Santos, 2020; Gindri dos Santos et al, 2021). However, the mechanisms by which naringin and naringenin affect offspring's mitochondria and whether such alterations might induce neurodevelopmental and behavioral defects that might prevent its use during pregnancy are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Naringin is isolated from citrus family plants such as lemons and oranges. Naringin is a 4',5,7-trihydroxyflavanone-7-rhamnoglucoside that tastes bitter and has shown beneficial effects in conditions such as diabetes, hepatic diseases and neurological diseases (7)(8)(9)(10)(11). It possesses antioxidant and anti-inflammatory properties, along with hypolipidemic activities (12).…”
Section: Introductionmentioning
confidence: 99%